RF magnetron sputtered Cd doped ZnO thin films for gas-sensing applications. Issue 4 (12th March 2017) - Vinoth, E.; Gowrishankar, S.; Gopalakrishnan, N.
ABSTRACT: RF magnetron sputtering has been employed to manufacture undoped and Cd doped (3%, 10%, and 20%) ZnO (CZO) films. X-ray diffraction (XRD) results revealed that the films have preferential orientation along (002) plane with hexagonal structure, and there are no secondary peaks. It is observed from the Hall Effect measurement that CZO films posses n- type conductivity, and the carrier concentration does not vary much with Cd concentration. On the other hand, the band gap estimated from Tauc's plot shows that band gap decreased with increase in Cd concentration. Red shift was observed in photoluminescence spectrum. Ethanol, methanol, and ammonia at gas concentration range of 50–200 ppm were exposed on the grown CZO films at different temperatures. Among the various concentrations of the films, CZO having 20% Cd exhibited better gas response toward methanol, while CZO with 10% Cd showed maximum gas response toward ammonia gas. This has been explained by grain boundary barrier (GBB) and double Schottky potential barrier mechanisms.